Extrinsic origin of ferromagnetism in single crystalline LaAlO₃ substrates and oxide films - Golmar, Federico (2008)
Commercial LaAlO₃ substrates were thermally cycled simulating a procedure similar to those followed during TiO₂ and SnO₂ dilute magnetic semiconductors’ film pulsed laser deposition. Ferromagneticlike behavior was found in some substrates, in which metallic iron impurities were detected by x-ray photoelectron spectroscopy and total reflection x-ray fluorescence measurements. A thorough experimental investigation, using high resolution techniques, showed that these impurities were introduced by the procedure used to fix the substrates to the oven silicon holders. It is suggested that magnetism observed previously in nominally pure SnO₂ films is of extrinsic origin.